Epitaxial Growth Of Gan On Gan Multi Quantum Well For The Deep Green Light Emitting Diode - Abdul Rais, Shamsul Amir (2022)
This work has focused on the effort of fabricating the deep green light emitting diode (LED). First, the multi-quantum well (MQW) that was expected to be able to emit a deep green wavelength was designed and fabricated. The MQW was first grown on a patterned sapphire substrate due to nucleation layer and lattice match which are nearest to the gallium nitride (GaN) substrate. The growth of six pairs of GaN/ InxGa1−xN layer that has 12.16/3.35 nm thickness was successfully carried out. The MQW has low crystal defect even when the indium ratio for InxGa1−xN layer growth was 9 times more than gallium. Previous research shows that a high indium ratio in GaN crystal growth would yield high strain but none of these have been observed. The MQW was later inserted into the full LED structure. The LED was grown on the GaN substrate. The resulting LED has good crystal quality, with dislocation of 8.7x107cm-2 . The photoluminescence (PL) spectrum also gives a good result, 568 nm which is in the deep green region. However, the device needed to be annealed to activate the p-type, and the wavelength blue-shifted greatly, 45nm after the annealing process. This prompted the introduction of the indium pre-flow technique to the later growth of the LED samples.